미국 영화 <프로포즈>에 나타난 로맨틱 코미디의 장르적 관습과 관객의 반응 -한국, 미국 관객의 영화 수용 양상의 국적별, 젠더별 차이를 중심으로 - 송민호; 염종희; 우정권; Song, Minho; Youm, Chonghee; Woo, Jeonggueon (한국콘텐츠학회 논문지, 13(3), 2013)
This study is on Hollywood's latest romantic comedy movie <The Proposal(2009)>, attempted to identify whether nationality or gender difference of the movie audience is affecting on their acceptance to the genre characteristics of Hollywood's romantic comedy. Most of Hollywood's romantic comedy movies are centered on attraction of female and male actors and its' formulated plot (boy-meets-girl, boy-loses-girl, boy-gets-girl structure). Although the movie <The proposal(2009)> is following the formulated romantic comedy plot, it shows a variation from the typical romantic comedy genre. In this thesis, based on audience research data, statistics and interrelationship analysis on audience value orientation, we elucidate how Korean and American, Female and Male movie audience have different preference to actors and characters in the movie <The Proposal(2009)> and representation of archetypal Hollywood romantic comedy happy ending such as propose and wedding scenes. 본 연구는 할리우드의 최근 로맨틱 코미디 영화인 <프로포즈(2009)>를 대상으로 하여 미국 할리우드 로맨틱 코미디 영화의 장르적 관습이 관객에게 수용되는 데 있어 관객의 국적이나 젠더가 그 수용 양상의 차이에 어떤 영향을 끼치고 있는가 하는 문제를 실증적으로 확인하고자 시도하였다. 할리우드 로맨틱 코미디 장르는 대부분 남녀 배우가 드러내는 매력을 중심으로 하여, 이들이 만나고 헤어지는 어느 정도 관습화된 플롯 위에 전개하는 특징을 갖고 있다. 영화 <프로포즈> 역시 이러한 관습화된 플롯 구조를 한편으로는 따르면서, 한편으로는 변주하고 있다. 본 논문에서는 영화 <프로포즈>에 등장하는 '배우'와 '등장인물'이라는 요소와, 할리우드의 일반적인 로맨틱 코미디 플롯에서 '사랑의 완성'으로 제시되는 '결혼식'과 '프로포즈'라는 요소가 한국과 미국이라는 국적과, 남성과 여성이라는 젠더에 따라서 어떤 다른 선호가 나타나는가 하는 바를 관객 반응을 묻는 설문조사와 통계를 통해 살펴보았고, 관객이 지향하는 가치들 사이의 상관성 분석을 통해 드러나는 의미를 해명하였다.